2019
DOI: 10.5817/cp2019-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Protective behavior against personalized ads: Motivation to turn personalization off

Abstract: Data collection and processing for personalized advertising has become a common practice in the industry. For this reason, regulators have been aiming to empower consumers to exercise more control over their data. Companies that collect and process data for personalized advertising are required to be transparent and among others, provide consumers with technical knowledge about the personalization process. At the same time, they have started offering settings to withdraw consent for processing data for persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…This provides a new level of insight into theories on persuasion knowledge 16 and ''hidden'' persuasion. [17][18][19] Although giving a name to an assistant leads users to see through the persuasive intent of a recommendation, it does not protect them against being persuaded. This is contrary to the traditional idea that more persuasion knowledge leads to less persuasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides a new level of insight into theories on persuasion knowledge 16 and ''hidden'' persuasion. [17][18][19] Although giving a name to an assistant leads users to see through the persuasive intent of a recommendation, it does not protect them against being persuaded. This is contrary to the traditional idea that more persuasion knowledge leads to less persuasion.…”
Section: Discussionmentioning
confidence: 99%
“…17 As people have less experience with receiving persuasive messages via voice-controlled devices than via screens, they are, therefore, likely to be less aware that a recommendation is, in reality, a persuasive attempt. 14,16,18 People's concerns and persuasion knowledge may subsequently influence the extent to which they are persuaded by recommendations made via an assistant. Previous research has demonstrated that awareness of persuasion attempts usually leads to more critical evaluation among adults, but not among young consumers.…”
Section: Modality: Different Types Of Voice and Screen-based Assistantsmentioning
confidence: 99%
“…A second method is the use of a custom-built browser plug-in designed to collect participants' online interactions and behaviors (e.g., Bodo et al, 2017;Haim and Nienierza, 2019;Strycharz et al, 2019). This approach has also been referred to as "data donation" (Krafft et al, 2019).…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…The growing intrusiveness of digital marketing has led to the development of more advanced attitudinal and behavioral coping tactics among consumers. For example, consumer concerns about online data privacy have led to new coping behaviors, such as setting up filters to withdraw consent for delivery of personalized advertising (Strycharz et al , 2019), installing ad blockers on computers and mobile devices to block all ads (Brinson and Britt, 2021) and unpairing wearable devices from smart phone applications to avoid third party data tracking and advertising (Brinson and Rutherford, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%